2011
DOI: 10.3844/ajptsp.2011.37.45
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Sub-acute Toxicity of <i>Crataegus Aronia Syn. Azarolus</i> (L.) Whole Plant Aqueous Extract in Wistar Rats

Abstract: Problem statement: Hawthorn comprises more than 200 species worldwide but very few species have been used medicinally. In Mediterranean region, the predominant species of the genus Crataegus is C. aronia syn. Azarolus (L). The extracts or tinctures prepared from the leaves, flowers and/or a fruit has been used traditionally for the treatment of different diseases including different cardiovascular problems. This species (C. aronia syn. Azarolus (L.)) has not been adequately studied. Thus, we aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…Furthermore, they help in reducing hemolysis of RBC and protecting their biological membranes from oxidative damage caused by free radicals (Kitagawa et al 1992;Asgary et al 2005). Therefore, this research seems to be in line with past research that MTE containing flavonoids is capable of being an antioxidant which can be used to maintain the heme iron and enhance erythropoiesis (Akah et al 2008;Uboh et al 2010;Shatoor 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, they help in reducing hemolysis of RBC and protecting their biological membranes from oxidative damage caused by free radicals (Kitagawa et al 1992;Asgary et al 2005). Therefore, this research seems to be in line with past research that MTE containing flavonoids is capable of being an antioxidant which can be used to maintain the heme iron and enhance erythropoiesis (Akah et al 2008;Uboh et al 2010;Shatoor 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Some investigators also report that the antioxidants present in plant extracts might trigger erythropoiesis. This seems to be in agreement with the present study as TCE has flavonoid that, as an antioxidant, might maintain the heme iron in its ferrous state (Akah et al 2007, Uboh et al 2010, Shatoor 2011.…”
Section: Blood Profilesupporting
confidence: 93%
“…Also, some investigators reported that the antioxidants present in the plant extract might trigger erythropoiesis and antioxidant activity (Shadu et al, 2006;Vargeshe et al, 2010;Lestari & Susanti, 2015). It seems in agreement with the present study as the TCL has flavonoids that capable as an antioxidant which may maintain the heme iron in its ferrous state and this could enhance erythropoiesis (Akah et al, 2008;Uboh et al., 2010;Shatoor, 2011).…”
Section: Blood Profilementioning
confidence: 99%